Z‐Scheme Heterojunction Functionalized Pyrite Nanosheets for Modulating Tumor Microenvironment and Strengthening Photo/Chemodynamic Therapeutic Effects. (21st October 2019) - Pan, Chao; Ou, Meitong; Cheng, Qinzhen; Zhou, Yun; Yu, Yongkang; Li, Zimu; Zhang, Fan; Xia, Dehua; Mei, Lin; Ji, Xiaoyuan
Abstract: A Z‐scheme heterojunction with high electron–hole pairs separation efficacy and enhanced redox potentials exhibits tremendous potential in photonic theranostics, but still remains unexplored and challenging. Herein, novel 2D thermally oxidized pyrite nanosheets (TOPY NSs) with FeS2 core and Fe2 O3 shell are fabricated combining ball grinding and two‐step probe sonication assisted liquid exfoliation under different solution and air environments. The Fe2 O3 shell and Fe 3+ /Fe 2+ inside TOPY NSs can both damage the tumor microenvironment through glutathione consumption and O2 production, and produce ·OH by Fenton reaction. More interestingly, a direct Z‐scheme heterojunction based on FeS2 core and Fe2 O3 shell is constructed, in which the electrons in the conduction band (CB) of Fe2 O3 are recombined with the holes in the valence band (VB) of FeS2, leaving stronger reduction/oxidation potentials in the CB of FeS2 and the VB of Fe2 O3 . Under irradiation of a 650 nm laser, the generation of ·O2 − from O2 and ·OH from OH − on the CB of FeS2 and VB of Fe2 O3, respectively, is largely enhanced. Furthermore, the NSs can be triggered by an 808 nm laser to generate local hyperthermia for photothermal therapy. Moreover, the fluorescent, photoacoustic, and photothermal imaging capabilities of the NSs allow multimodal imaging‐guided cancer treatment. Abstract : Two‐dimensional thermally oxidized pyrite nanosheets (TOPY NSs) with a FeS2 core and Fe2 O3 shell‐based Z‐scheme heterojunction are fabricated through a smart exfoliation approach. The nanoplatform based on PEGylated TOPY NSs exhibits multiple features, such as tumor microenvironment modulation, efficient reactive oxygen species production and photothermal conversion, high tumor site accumulation, good biocompatibility, and multimodal imaging guided‐cancer treatment.